Clean environment - Jones, Sara (Wayland Hove, 1993)
"Environment" by Sara Jones is a 48-page hardcover book published in 1993 as part of the Human Rights series. The book highlights the fragility of the Earth and examines various aspects of environmental abuse, as well as the steps being taken toward reform. It is illustrated throughout with color and black-and-white photographs